-4(1+7x)+6x=x-4

Simple and best practice solution for -4(1+7x)+6x=x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(1+7x)+6x=x-4 equation:


Simplifying
-4(1 + 7x) + 6x = x + -4
(1 * -4 + 7x * -4) + 6x = x + -4
(-4 + -28x) + 6x = x + -4

Combine like terms: -28x + 6x = -22x
-4 + -22x = x + -4

Reorder the terms:
-4 + -22x = -4 + x

Add '4' to each side of the equation.
-4 + 4 + -22x = -4 + 4 + x

Combine like terms: -4 + 4 = 0
0 + -22x = -4 + 4 + x
-22x = -4 + 4 + x

Combine like terms: -4 + 4 = 0
-22x = 0 + x
-22x = x

Solving
-22x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-22x + -1x = x + -1x

Combine like terms: -22x + -1x = -23x
-23x = x + -1x

Combine like terms: x + -1x = 0
-23x = 0

Divide each side by '-23'.
x = 0

Simplifying
x = 0

See similar equations:

| 7(2-x)=7x | | 8d-20=4(2d-5) | | -6*20= | | 5(4k-7)=1+8k | | 2x-4+8x=-4 | | -5y+18=-2y+12 | | 7x-7=5(x+4) | | 1/3(2x-6) | | -4.36+1.2(2.8+-3.5)= | | 2/3(3X-12)+1/4(8X+4) | | x/3-4=x/5-6 | | (-1/4p)+4=(3/4p)+8 | | k^2-16k+48=0 | | 80-6n=4n | | -27=b+(-14) | | 21-1/22(3x)=14-1/22(2x) | | 1/2(2x+4x)-2x=-5 | | -3(x+4)-43=8-39 | | y-50=-5.66666667(x-10) | | 3/8y-10=y | | 3(1/4) | | 3y-45=3(3y-5) | | -9x+y=-5 | | 2x-5-1=17 | | x-.15x=255000 | | 9-x/3=-1 | | N+(-6)=7 | | 5(x+2)-3=4(x+4) | | 1/2(4y+8)+2/3(9y-12)=16 | | 12+4x=12x | | 3/4(n-4)=3/8(n-3) | | -24/-6 |

Equations solver categories